3‐Trifluoromethylated Coumarins and Carbostyrils by Radical Trifluoromethylation of ortho‐Functionalized Cinnamic Esters. Issue 2 (7th December 2016) - Chaabouni, Slim; Simonet, Florent; François, Alison; Abid, Souhir; Galaup, Chantal; Chassaing, Stefan
Abstract : A method for the trifluoromethylation of ortho ‐hydroxycinnamic esters was developed to achieve the regioselective synthesis of 3‐trifluoromethylated coumarins. The reaction was performed by using the Togni reagent as the CF3 source under mild conditions and showed good functional‐ group tolerance. The scope of this copper‐mediated method was further expanded to the synthesis of 3‐trifluoromethylated carbostyrils starting from ortho ‐aminocinnamic derivatives. Interestingly, a sequential one‐pot synthesis of 3‐trifluoromethylated coumarins starting from salicylaldehydes was further developed. The mechanism of this cascade reaction was explored, and a radical pathway was found to be consistent with the obtained results. Abstract : A method for the regioselective synthesis of 3‐trifluoromethylated coumarins and carbostyrils by the direct trifluoromethylation of appropriately substituted ortho ‐functionalized esters is described. The reaction proceeds by using the Togni reagent as the CF3 source under mild conditions and shows good functional‐group tolerance.